Why men don't listen & women can't read maps - Pease, Allan; Pease, Barbara (India : Manjul Publishing House, 2001)
The classic international bestselling book. Allan and Barbara Pease spotlight the differences in the way men and women think.
Includes reference.
Keywords: Gender identity; Man-woman relationships; Sex differences (Psychology).